2007
DOI: 10.1007/s10535-007-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzylaminopurine and irradiance on cytokinin contents, α-tubulin gene expression and cucumber cotyledon expansion

Abstract: The fluctuation of endogenous cytokinins was determined in the excised cucumber (Cucumis sativa L.) cotyledons incubated with benzylaminopurine (BA) under irradiance or in darkness. The data indicated that light stimulated the cotyledon expansion compared with dark and BA further enhanced the expansion of cotyledons. However, only BA treatment markedly increased the contents of endogenous cytokinins and induced α-tubulin gene expression. Actinomycin D, a well-known inhibitor of gene transcription, strongly inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, a relationship between cytokinin and light in inducing cell division in green alga is not fully understood. It was only reported by Li and Ma (2007) that BA applications under dark conditions markedly increased the contents of endogenous cytokinins and induced a-tubulin gene expression in cucumber cotyledon. Therefore, the normal cell expansion and mitosis can contribute to cotyledon growth and development in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…However, a relationship between cytokinin and light in inducing cell division in green alga is not fully understood. It was only reported by Li and Ma (2007) that BA applications under dark conditions markedly increased the contents of endogenous cytokinins and induced a-tubulin gene expression in cucumber cotyledon. Therefore, the normal cell expansion and mitosis can contribute to cotyledon growth and development in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kudoyarova et al (2007) recently observed decrease in CK content in tomato leaf tissue up to 46 % during water stress but no changes in xylem sap CK content. Treatment of cucumber cotyledons with CK benzyladenine (BA; 20 μM) increased content of endogenous CKs (Li and Ma 2007). In bean plants, pre-treatment with BA ameliorated effects of water stress on gas exchange parameters (Pospíšilová and Baťková 2004) and BA application also improved recovery of drought stressed bean plants after rehydration (Rulcová and Pospíšilová 2001).…”
Section: Introductionmentioning
confidence: 99%
“…51 During the life cycle of eukaryotic cells, microtubules are capable of performing various tasks which may relate to cell expansion and cell division. 52,53 Li & Ma 54 found that light enhanced the cucumber (Cucumis sativa L.) cotyledon expansion as compared with dark and benzylaminopurine (BAP) further enhanced the expansion of cotyledons. In cucumber cotyledon expansion, BAP treatment markedly increased the contents of endogenous cytokinins and induced α-tubulin gene expression.…”
mentioning
confidence: 99%